Phenolic profile and antioxidant activities of the low-alcoholic fermented beverage processed from Finnish strawberries (Fragaria × ananassa) - Alfaro Caso, Pierina (My University, 2020)
Strawberry (Fragaria × ananassa) is commercially the most important berry in Finland, considering both cultivation area and yield. The popularity of this berry can be attributed to its appealing characteristics, as well as nutritional and health promoting components, such as anthocyanins and ellagitannins. This berry has a very short shelf-life, leading to significant economic losses if it’s not brought to the market quickly. Processing strawberries into fermented beverages could be considered a solution, as fermentation increases stability of processed foods, extends shelf-life and enhances some nutritional and organoleptic qualities. With this aim in mind, a novel low-alcoholic fermented beverage (LAFB) processed from Finnish strawberry was developed in this study. The present study aimed to investigate the phenolic profile and antioxidant activ- ities of this LAFB. The composition and content of anthocyanins and ellagitannins were investigated by using LC-DAD. The antioxidant activities of LAFB were de- tected by using DPPH and FRAP, as well as the determination of total phenolics by using Folin-Ciocalteu method. The effects of different cultivars (Polka, Lumotar and Honeoye) and yeast strains (Saccharomyces cerevisiae and Torulaspora delbrueckii) on the LAFB were also evaluated. Among anthocyanins, pelargonidin-3-glucoside was the most abundant in all the samples. The total anthocyanin of LAFB was expressed as pelargonidin-3-glucoside, and it was significantly higher (p<0.001) in cultivar Honeoye (0.11 mg/mL), regard- less of the yeast used in the fermentation. After fermentation, the loss of antho- cyanins was up to approximately 50%, where S. cerevisiae caused a significantly major loss (p<0.01) than T. delbrueckii, regardless of the cultivar. The juice of cultivar Polka had a higher content of ellagitannins (0.0221 mg/mL, p<0.001), fol- lowed by Honeoye (0.0172 mg/mL) and Lumotar (0.0154 mg/mL). LAFB of cultivar Honeoye presented the highest phenolic content expressed in gallic acid equivalents (≈ 511 mg/L), as well as a significantly higher antioxidant capacity (p<0.001) in both DPPH (≈0.41 mg/mL of gallic acid eq.) and FRAP (≈ 420 uM/mL trolox equivalents) assays.
Keywords: Anthocyanins, Antioxidant Activity, Ellagitannins, Fermentation, Phenolics, Strawberries.